Antifungi Tanaman Komoditas Hortikultura Spesises Cabai Rawit Pada Formulasi Dan Sediaan Spray Kombucha Bunga Telang Dan Bunga Kecombrang Sebagai Produk Bioteknologi Pertanian Dan Farmasi - Firman Rezaldi; Roni Gumilar; Agan Syahrial; Tri Yudianto; Ratna Fitry Yenny; Usman Setiawan (Jurnal Kesehatan Tujuh Belas (Jurkes TB), 2025)
Horticultural commodity plants are commodities that play an important role in meeting food needs, one of which is red chili. One of the weaknesses of horticultural products is that they are easily damaged, have a short shelf life, and are easily contaminated by pathogenic fungi. Pathogenic fungi that have the potential to contaminate red chili plants include Colletotrichum capsicii, Cercospora capsici, and Phytophthora capsici. The solution to overcome the epidemiology of contamination of these three pathogenic fungi is by utilizing the fermentation waste of kombucha from butterfly pea flowers and torch ginger flowers in the form of formulations and spray preparations. This study aims to compare spray waste from butterfly pea flowers and torch ginger flowers at concentrations of 20%, 30%, and 40% in inhibiting the growth of the three pathogenic fungi for red chili plants. This study is an experimental laboratory study which provides Na.CMC as a negative control and the antibiotic ketonazole as a positive control then provides fermentation waste from butterfly pea flowers and torch ginger flowers in concentrations of 20%, 30%, and 40%. The inhibition test was carried out through disc diffusion. Data analysis was carried out through one way ANOVA. The results of the study based on one way ANOVA test at each P value <0.05 continued with post hoc test has proven that kombucha waste of butterfly pea and torch ginger flowers at a concentration of 40% is not significantly different from 20% and 30% as an antifungal Colletotrichum capsicii, Cercospora capsici, and Phytophthora capsici. The conclusion in this study is that kombucha waste of butterfly pea flowers at all concentrations is higher when compared to kombucha waste of torch ginger flowers as a product of agricultural and pharmaceutical biotechnology and antifungal.